2003
DOI: 10.1029/2003ja010029
|View full text |Cite
|
Sign up to set email alerts
|

A statistical comparison of interplanetary shock and CME propagation models

Abstract: [1] We have compared the prediction capability of two types of Sun-Earth connection models: (1) ensemble of physics-based shock propagation models (STOA, STOA-2, ISPM, and HAFv.2) and (2) empirical CME propagation (CME-ICME and CME-IP shock) models. For this purpose, we have selected 38 near-simultaneous pairs of coronal mass ejections (CMEs) and metric type II radio bursts. By applying the adopted models to these events, we have estimated the time difference between predicted and observed arrivals of interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 41 publications
(74 reference statements)
3
44
0
Order By: Relevance
“…There are several promising computer codes under development, with very encouraging results (e.g. Riley et al, 2001;Linker et al, 2003;Mozer and Briggs, 2003;Cho et al, 2003;Fry et al, 2003;Manchester et al, 2004;Odstrcil et al, 2004;Riley and Crooker, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…There are several promising computer codes under development, with very encouraging results (e.g. Riley et al, 2001;Linker et al, 2003;Mozer and Briggs, 2003;Cho et al, 2003;Fry et al, 2003;Manchester et al, 2004;Odstrcil et al, 2004;Riley and Crooker, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…It is very meaningful in that it can give us about 2-3 days of advance notice to prepare for geomagnetic storms. Other studies, still in very early stages [Dryer, 1998], use physics-based models that employ observations of flares or CME occurrences and coronal shock-induced metric radio frequency drifts [Cho et al, 2003;Fry et al, 2003;Odstrcil, 2003;Dryer et al, 2004;McKenna-Lawlor et al, 2006] to predict CME or their shocks' arrivals at Earth. These studies use such observations (such as CME cone shapes and ad hoc overpressure or momentum pulses) to mimic the basically unknown physical processes in the originating form of solar activity.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Gopalswamy et al (2001a); Schwenn et al (2001); Wang et al (2002); Cho et al (2003) have derived more complicated relationships between the travel time and the initial CME velocity. Regarding location of the source, Wang et al (2002) and Zhang et al (2003) found that CMEs responsible for major geomagnetic storms come mostly from the western hemisphere and within a latitude strip of ±30 • around the equator.…”
Section: Predicting Icmesmentioning
confidence: 99%
“…As recalled by Jacobs et al (2005), the frequency drift of the resulting type II radio emissions is related to the dynamics of the shock and the related CME, as the density of the ambient solar wind drops with increasing distance from the Sun. However, the relationship between metric to kilometric type II bursts and CME-produced shocks is not strict (Claßen and Aurass, 2002;Wen and Wang, 2004). Type II events are often accompanied by a parallel burst at the first harmonic (approximately double the frequency) of the main burst.…”
Section: Coronal Mass Ejections (Cmes)mentioning
confidence: 99%